Studies of Staphylococcus aureus FabI inhibitors: fragment-based approach based on holographic structure–activity relationship analyses. (February 2017) - Kronenberger, Thales; Asse, Leonardo Rander; Wrenger, Carsten; Trossini, Gustavo Henrique Goulart; Honorio, Kathia Maria; Maltarollo, Vinicius Gonçalves
Aim: FabI is a key enzyme in the fatty acid metabolism of Gram-positive bacteria such as Staphylococcus aureus and is an established drug target for known antibiotics such as triclosan. However, due to increasing antibacterial resistance, there is an urgent demand for new drug discovery. Recently, aminopyridine derivatives have been proposed as promising competitive inhibitors of FabI.Methods: In the present study, holographic structure–activity relationship (HQSAR) analyses were employed for determining structural contributions of a series containing 105 FabI inhibitors.Results & conclusion: The final HQSAR model was robust and predictive according to statistical validation (q 2 and r 2 pred equal to 0.696 and 0.854, respectively) and could be further employed to generate fragment contribution maps. Then, final HQSAR model together with FabI active site information can be useful for designing novel bioactive ligands.